A new approach to the study of the size and the geometry effect on compressive strength in concrete - Ángel De La Rosa; Gonzalo Ruiz (Results in Engineering)
This study investigates the relationship between the compressive strength of cylindrical and cubic concrete specimens, focusing on the influence of specimen shape, size, concrete type, and casting orientation. While the effect of specimen size and shape on compressive strength is well-established, discrepancies persist in the literature regarding the strength relationship between different specimen geometries. To address these discrepancies, this article introduces an innovative Fracture Mechanics-based model that accounts for the size and geometric effects of concrete specimens. By analyzing experimental data from previous studies on both vibrated (VC) and self-compacting concrete (SCC) (water-cement ratios ranging from 0.28 to 0.67 for VC, and from 0.35 to 0.43 for SCC), this research proposes a model to calculate the conversion factor between cylinder and cubes.Results show discrepancies between the fib Model Code 2010 predictions and experimental data, emphasizing the importance of incorporating Fracture Mechanics parameters, such as fracture energy, for accurate strength predictions. While the Fracture Mechanics model works well for VC, it does not predict cylinder-to-cube strength relationships for SCC as effectively, likely due to its unique properties. To address this, a new conversion relationship for cylinder-to-cube compressive strength, also based on Fracture Mechanics, is proposed, offering a more accurate and reliable method for evaluating concrete strength. This model defines precise conversion relationships between the compressive strengths of specimens with different geometries, enhancing the understanding of Fracture Mechanics in concrete technology and having significant implications for improving structural design codes. Further experimental validation and refinement of the model are planned.